2020
DOI: 10.1111/apa.15174
|View full text |Cite
|
Sign up to set email alerts
|

Randomised oral stimulation and exclusive breastfeeding duration in healthy premature infants

Abstract: Aim Although exclusive breastfeeding is recommended for all newborn in the first 6 months of life, only 13% of Danish premature infants complies with this. This trial aimed to examine whether oral stimulation prolonged exclusive breastfeeding in premature infants. Method A randomised controlled trial was conducted at the Neonatal Intensive Care Unit, Hvidovre Hospital, Denmark between 2016 and 2018. Systematic oral stimulation was performed by the parents after training by occupational therapists. Primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Sasmal et al ( 8 ) observed higher breastfeeding rates with PIOMI at 1 month after discharge. Skaaning et al ( 9 ) evaluated the effect of a parent-administered PIOMI-based oral motor stimulation method. Both studies, however, could not establish a significant impact on exclusive breastfeeding with PIOMI.…”
Section: Discussionmentioning
confidence: 99%
“…Sasmal et al ( 8 ) observed higher breastfeeding rates with PIOMI at 1 month after discharge. Skaaning et al ( 9 ) evaluated the effect of a parent-administered PIOMI-based oral motor stimulation method. Both studies, however, could not establish a significant impact on exclusive breastfeeding with PIOMI.…”
Section: Discussionmentioning
confidence: 99%
“…Pimenta et al (2008) found that 27% of the babies in their experimental group (non-nutritional sucking and OMS) and 10% of the babies in the control group continued to suck after 6 months. On the contrary, some studies showed that oral stimulation does not affect maintaining breastfeeding (Skaaning et al, 2020). The differences between studies may be due to the gestational week of the preterm babies sampled, as the infant’s contribution to the breastfeeding process depends on maturity, muscle strength, and neonatal reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…The present qualitative study recruited participants among cohorts in a randomized control trial (RCT), titled “Breastfeeding duration in premature infants. Influence of oral stimulation intervention, the infant's suction and maternal concerns.” The RCT study included 174 mothers of 211 infants and showed no effect of oral stimulation on exclusive breastfeeding 6 month after discharge 28. The study was approved by the Danish Committees on Health Research Ethics (ID 60112) and registered at the Danish Data Protection Board (ID AHH-2015-106) and ClinicalTrials.gov (ID NCT02952950).…”
Section: Methodsmentioning
confidence: 99%